First year pharmacy students as health coach in the management of hypertension - Pounds, Kimberley; Offurum, Angela; Moultry, Aisha Morris (Pharmacy Education, 2015)
Introduction: Learning how to be a health mentor is an experience that can provide pharmacy students with skills necessary to adequately fulfil their role in prevention and wellness. Description: This paper describes a service-learning project that involved training 103 first year pharmacy students as health mentors for a pilot program designed to support the prevention or management of risks for heart disease in African Americans. Texas Southern University’s College of Pharmacy and Health Sciences partnered with the American Heart Association to implement the AHA’s Heart 360 (Get to Goal) program. Evaluation: Both quantitative and qualitative data were collected to assess students’ experiences. Although students were confident in their abilities to perform coaching skills (85%), they did not feel comfortable educating patients about hypertension (86%). Future Plans: Changing the structure of the skills-based portion of the training from a large to small group will allow faculty to observe each students’ readiness to serve as health coach. Including other health profession students will expand the impact of the Healthy People 2020 goals.